A gene responsible for autosomal dominant auditory neuropathy (AUNA1) maps to 13q14–21 - Kim, T B; Isaacson, B; Sivakumaran, T A; Starr, A; Keats, B J B; Lesperance, M M (Journal of medical genetics, 2004)
The Institutional Review Boards of the University of Michigan Medical School, Louisiana State University Health Sciences Center, and the University of California at Irvine approved the study, and informed consent was obtained from all subjects. Numerous candidate genes of interest map to the AUNA1 interval (UCSC Genome Browser: http://genome.ucsc.edu ) including diaphanous homolog 3 (DIAPH3), several protocadherins (PCDH9 (MIM 603581), PCDH8 (MIM 603580), PCDH17, and PCHD20), and genes implicated in protein and/or ion transport (WD repeat and FYVE domain containing 2 (WDFY2) and potassium channel regulator gene, KCNRG (MIM 607947)).